Estudio del enlace inductivo transcutáneo en el suministro de energía en dispositivos electrónicos implantados. - Muñoz, R.; Leija, L.; Flores, J.; Álvarez, Ja.; Minor, A.; Reyes, J. L. (Revista Mexicana de Ingenieria Biomedica, 2001)
The experimental analysis of the performance of a system of transcutaneous inductive link is described in this article, this inductive link was developed to supply energy to an implantable biotelemetry System. In order to evaluate in vivo the link efficiency, the receptor coil, covered with silicone of medical degree was implanted in rabbit by a period of six months. The obtained results show that the layer of fibrous tissue formed around the one implants, it reduced the efficiency of the link in 30%, besides affecting the tolerance to the lateral displacement among the external coil (transmitter) and the implanted coil (receptor). With their respective cautions, this system of transcutaneous inductive link can be used for the energy supply to implantable electronic devices, avoiding in this way, the employment of batteries.